ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTERNET FINANCIAL AND SUSTAINABILITY REPORTING (IFSR) PADA PERUSAHAAN PERAIH INDONESIAN SUSTAINABILITY REPORTING AWARD (ISRA) TAHUN 2017 - Purbandari, Theresia; Immanuela, Intan (Widya Warta, 2019)
This study aims to prove empirically that size, profitability, leverage, and outside party ownership structures influence the internet financial and sustainability reporting. The data used in this study was the winner of the Indonesian Sustainability Reporting Award in 2017. The sampling technique was purposive sampling and data obtained as many as 25 companies that met the sample criteria. Hypothesis testing technique is multiple linear regression analysis. Hypothesis test results indicate that size, profitability, leverage, and outside party ownership structures do not affect the internet financial and sustainability reporting.